Performance efficiency of a predictive scheme into publish/subscribe. (2018) - Abdennadher, Fatma; Jemaa, Maher Ben
Nowadays, the importance of mobility into publish/subscribe systems has increased due to the increased number of applications into handheld devices. For offering the best service to mobile subscribers, mobility management is very much necessary. Previous mobility management schemes suffer from an increase in the transfer delay, message loss and network load. In this paper a predictive mobility management scheme has been proposed to overcome these problems. The proposed scheme selects the most probable candidate's brokers for being the caching points. This selection is based on the probabilities of movements higher than the threshold value. The proposed scheme and previous proactive scheme have been compared through set experiments. Performance comparison shows that our approach performs better than previous works in terms of messages loss, network load and transfer delay under distinct factors such as frequency of movements, period of disconnection and publication rate.